Land cover change instead of solar radiation change dominates the forest GPP increase during the recent phase of the Shelterbelt Program for Pearl River. (March 2022) - Zhang, Xiaoyu; Zhou, Yanlian; He, Wei; Ju, Weimin; Liu, Yibo; Bi, Wenjun; Cheng, Nuo; Wei, Xiaonan
Highlights: Forest GPP change in the area of the Shelterbelt Program for Pearl River was studied. The contributions of land cover and climate changes in two periods were disentangled. During 2001–2010, solar radiation dominated a slow increase of forest GPP. During 2011–2018, land cover change became the primary contributor of a fast GPP increase. Afforestation ecological benefits emerge after a certain time period and forestation scale. Abstract: China has implemented a series of large-scale afforestation projects to improve its ecological environment in recent decades. Meanwhile, the climate conditions in China have changed substantially. However, whether afforestation or climate change dominates vegetation gross primary production (GPP) in different stages of such afforestation projects is not clear. Here, taking the region of the Shelterbelt Program for Pearl River (SPPR) as the study area, we conducted six scenario simulations using the two-leaf light use efficiency (TL-LUE) model to decouple the effects of land cover change (LCC) and climate factors, i.e., solar radiation (Rad), vapor pressure deficit (VPD), and air temperature (Ta), on forest GPP, and disentangled the impact of various factors on forest GPP in Phase II (2001–2010) and Phase III (2011–2018). We found that industrialization and urbanization slightly changed the total forest area, partly offsetting the ecological benefits of the afforestation project in Phase II, and forest GPP increased slowly. As a result, Rad became the dominant factor of forest GPP increase (the cumulative contribution of 25.68 TgC in 10 years, accounting for 33.51%). In contrast, in Phase III, due to the further expansion of the afforestation area and the natural growth of earlier planted forests, the forest GPP increased rapidly, as did the contribution of LCC. Finally, LCC replaced Rad to become the primary contributor (the cumulative contribution of 114.42 TgC in 8 years, accounting for 60.51%) to the forest GPP increase. During the whole study period, Ta contributed insignificantly to the variation in forest GPP, while to some extent VPD decreased the forest GPP (−12.90% and −4.11% of the contributions in the two phases, respectively). The results suggest that the emergence of ecological benefits of afforestation projects requires a certain time length and forestation scale. Our study provides a basis for formulating effective land use policies.